Pembuatan Sistem informasi Administrasi pada UD. S - Fenycia Noviani Tjhandra; Djoni Haryadi Setiabudi; Silvia Rostianingsih (Jurnal Infra, 2015)
UD. S is a business engaged in the sales of a wide range of household cleaning equipment, such as brooms, mops, duster, cloth, mat, hanger, and so on. UD. S makes purchases from suppliers and then resells them with a profit for the company, so that in this case the UD. S does not have its own production of goods. In the sales process, UD. S serves retail and wholesale. During this time, UD. S still perform the process manually allowing the occurrence of errors in entering data or errors in calculation and also more time consuming.This administration system application can help support and improve company performance. Administration system application built using the MySQL database and PHP programming language, HTML, and JavaScript.